Motions of particles and red blood cells in a bifurcation: comparison between experiments and numerical simulations - Lagoela, Marco (2009)
The blood flow dynamics in microcirculation depends strongly on the microvascular networks composed with short irregular vessel segments which are linked by numerous bifurcations. This paper presents the application of a confocal micro-PTV system to track RBCs through a rectangular polydimethysiloxane (PDMS) microchannel with a bifurcation. By using a confocal micro-PTV system, we have measured the effect of bifurcation on the flow behaviour of both fluorescent particles diluted in pure water and RBCs in concentrated suspensions. After performing simulations with the commercial finite element software package POLYFLOW®, some experimental results were compared with the numerical results. Our preliminary qualitative results suggest that the in vitro blood flowing (Re = 0.007) through a bifurcation seems to have a tendency to behave more closely as a Power law model than as a Carreau or Newtonian model.